Analisis Kekuatan Perkerasan Landas Pacu Bandar Udara Juanda Dengan Metode FAA dan Software COMFAA - Istiar .; S. Kamilia Aziz (Jurnal Aplikasi Teknik Sipil, 2021)
Runway was an important the airport facilities, used for the movement of arrival and departure aircraft. To provide optimal service, the runway pavement structure had to evaluated periodically. This paper presented the results of the runway pavement strength analysis with the FAA Method and calculated by COMFAA. The primary data were used soil investigation data, pavement core drill and georadar survey. The samples of primary data is divided into 10 segments of runway length. Meanwhile, the secondary data was used aircraft departures in last 5 years. The results of the analysis showed that the existing thickness of the runway pavement structure along 1100 meters from the threshold of Runway 10 was able to defense the gross weight of aircraft until the life design of the runway pavement structure and the PCN value is greater than ACN. Vice versa for the remaining runway length to the threshold of Runway 28.